Speech delay: some possible factors (a research on 3-6 years old children) - Meta Keumala; Zahratul Idami (Politeknik Negeri Bali, 2021)
This qualitative research was to describe the language development of children who indicated speech delay and to find out what factors make these children delay in speech. The data were got from a depth-observation of three children indicating speech delay; 4 and 6 years old children of the first writer’s, and a 3 year- old-child of the writer’s friend’s. The observation was done since the children were indicating speech delay until November 2019. Besides, an open-ended interview was also administered with the mother of the youngest subject. The data were analyzed by using the normal pattern of children’s speech development by Blum and Baron (1997) and main possible factors of speech delay as presented by Shetty (2012). This research found that the subjects experienced speech delay at the ages of 1 year. However, the development of speaking started to increase at the age of 3. Some factors that caused the condition to the subjects were maturation delay, developmental expressive aphasia, bilingualism, and social deprivation.